(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Glass ionomer cement (GIC) has become a fundamental material in contemporary dentistry due to its unique properties and diverse clinical applications. This article provides an overview of the composition, properties, and clinical uses of GIC, highlighting its significance in restorative, pediatric, orthodontic, and prosthodontic dentistry. Key advancements in GIC technology, including resin-modified formulations, nano-ionomer technology, and extended-release formulations, are discussed.